The Effect of HVP Training in Vowel Perception on Bilingual Speech Production - Kangatharan, Jayanthiny; Giannakopoulou, Anastasia; Uther, Maria (Research in English Language Teaching, 2021)
Prior investigations (Giannakopoulou, Uther, & Ylinen, 2013) have indicated high variability phonetic training intervention can help L2 English adult learners change the perception of vowels such that they shift their attention to primary cues (spectral features) rather than secondary cues (e.g. duration) to correctly identify vowels in L2. This experiment explores if high-variability training impacts on L2 adult learners’ production of L2 speech. Production samples from a prior experiment were used to conduct ratings of accuracy (Giannakopoulou, 2012). In the current experiment, the production samples were transcribed and rated for accuracy by twenty native English listeners. The intelligibility levels of L2 learners’ speech samples as indexed by higher accuracy in transcription were observed as having been rated higher following training than prior to training. This indicates that high-variability phonetic training helps to turn L2 learners’ perceptual benefit of enhancing their identification and discrimination of non-native contrasts into a tangible benefit when producing speech in L2. The implications of the results are considered with regard to theories on the connection between speech production and perception, and Flege (1995) Speech Learning Model.